Report of the Working Group on Command Area Development Programme (CADP) for 10th Five-Year Plan (2002-2007) - Planning Commission (Planning Commission, 2001)
The Report of the Working Group on Command Area Development Programme (CADP) for the 10th Five-Year Plan (2002–2007) outlines strategies for enhancing irrigation efficiency, equitable water distribution, and agricultural productivity in India. It emphasizes bridging the gap between irrigation potential created and utilized through integrated water management, field-level interventions, and the Warabandi system. Key recommendations include strengthening Participatory Irrigation Management (PIM) by empowering Water Users Associations (WUAs), prioritizing the completion of ongoing projects, addressing waterlogging and drainage issues, and including minor irrigation projects. The report identifies funding constraints and calls for increased financial allocations, with a proposed budget of approximately ₹11,551 crores. Evaluations across states reveal mixed success in PIM implementation, highlighting inefficiencies, underutilized water supply, and variable WUA performance. The report underscores that effective farmer participation, capacity building, institutional reforms, and robust funding are critical to achieving sustainable irrigation management, higher agricultural output, and improved socio-economic conditions in rural India.
Planning Commission Government of India New Delhi September, 2001
Planning Commission Government of India New Delhi September, 2001
Keywords: Command Area Development Programme; CADP; Participatory Irrigation Management; Water Users Associations; Irrigation Efficiency; Agricultural Productivity; Warabandi System; Waterlogging Management; Farmer Participation; Rural Employment; Irrigation Infrastructure; 10th Five Year Plan